INTESTINAL ANGIONEUROTIC EDEMA ASSOCIATED WITH PERINDOPRIL ADMINISTRATION. (June 2018) - Wojciechowska, E.; Gryglas, P.; Jedrusik, P.; Dul, P.
Abstract : Objective: To report a case of rare severe adverse reaction to an inhibitor of angiotensin-converting enzyme (iACE). Design and method: A 44-year-old female with a history of hypertension for 5 years, asthma, and atopy was admitted to a local emergency department due to diffuse abdominal pain with vomiting and diarrhea lasting for 2 days. A few days earlier, perindopril was administered due to suboptimal BP control. The first dose of iACE was followed by lower abdominal pain, urgency to defecate associated with difficulties in passing the stool. After the next dose of iACE, she developed severe, gradually increasing, diffuse abdominal pain with concomitant nausea, vomiting, and diarrhea. She arrived to emergency room and signs of peritonitis were present on physical examination. Acute abdomen was diagnosed and CT scan ordered which showed diffuse infiltrates within the small intestine and mesentery, with free abdominal fluid but no signs of perforation. Gastrointestinal angioneurotic edema related to iACE was suspected and patient was transferred to department of medicine. On admission to the medical unit, the patient was moderately unwell, conscious, with BP 170/100 mmHg, HR 110 bpm, SaO2 99% on room air, and normal body temperature. Physical examination of abdomen revealed reduced bowel sounds, guarding and tenderness on palpation, especially in the mid-abdomen with rebound tenderness. Laboratory tests showed elevated WBC (13, 600/mm3) and CRP (22 mg/L). Results: Perindopril was withdrawn, the patient received antihistamines, analgesics, and intravenous fluids, with improvement of the patient's condition and reduction of pain and levels of inflammation markers. Abdominal CT scan done after 5 days showed resolution edematous lesions in small intestine. The patient was discharged home in good condition, without abdominal pain, and with good BP control. The final diagnosis was gastrointestinal angioneurotic edema associated with iACE treatment. Conclusions: Isolated angioedema of small intestine due to iACE administration is rare complication but creates diagnostic problems and may imitate acute abdomen. Prompt and accurate diagnosis may prevent unnecessary investigations and surgical interventions.